2016
DOI: 10.5005/jp-journals-10005-1332
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocating vs Rotary Instrumentation in Pediatric Endodontics: Cone Beam Computed Tomographic Analysis of Deciduous Root Canals using Two Single-file Systems

Abstract: Background: Primary root canals are considered to be most challenging due to their complex anatomy. "Wave one" and "one shape" are single-file systems with reciprocating and rotary motion respectively. The aim of this study was to evaluate and compare dentin thickness, centering ability, canal transportation, and instrumentation time of wave one and one shape files in primary root canals using a cone beam computed tomographic (CBCT) analysis.Study design: This is an experimental, in vitro study comparing the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 15 publications
2
55
0
5
Order By: Relevance
“…Reciprocating files works by back and forth motion that reduces the number of endodontic mishaps through instrument separation, thereby improving the safety of the shaping procedures [20]. Prabhakar et al, stated that the reciprocating single file system were faster and safer for canal preparation as the reciprocating motion does not over engage the dentin and reaches the working length faster than rotational motion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocating files works by back and forth motion that reduces the number of endodontic mishaps through instrument separation, thereby improving the safety of the shaping procedures [20]. Prabhakar et al, stated that the reciprocating single file system were faster and safer for canal preparation as the reciprocating motion does not over engage the dentin and reaches the working length faster than rotational motion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported longer times for instrumentation with rotary systems compared to the manual, in which he considered it as a matter of operator's experience . Regarding the risk of canal transportation, less effect was found using a reciprocating system compared to a continuous rotary system in primary teeth …”
Section: Discussionmentioning
confidence: 99%
“…9 Regarding the risk of canal transportation, less effect was found using a reciprocating system compared to a continuous rotary system in primary teeth. 29 Regarding anatomic features, root canals of primary maxillary central incisors are flat, ribbon-shaped, whereas the rotary instruments have a spherical shape with a taper descending to the apex. Therefore, a percentage of noninstrumented areas will always be expected when using these instruments, as verified for permanent root canals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physics behind reciprocating motion is based on the “law of action and reaction,” which results in a balanced force during canal instrumentation, as theorized by Prabhakar et al . [ 4 ] The first study experimenting with an alternating movement was that of Yared in 2008, which used the ProTaper F2 instrument (Dentsply/Maillefer) in a reciprocating movement. [ 13 ] The reciprocating movement minimizes torsional and flexural stresses, increases the canal centering ability, and reduces the taper lock of the instrument within the canal.…”
Section: Discussionmentioning
confidence: 99%
“…Single-file rotary systems may be classified on the basis of their motion into rotating and reciprocating files. [ 4 5 ]…”
Section: Introductionmentioning
confidence: 99%